A virtual reality loop and wire game for stroke rehabilitation - Christou, Chris; Michael-Grigoriou, Despina; Sokratous, Dimitris; Tsiakoulia, Marianna (My University, 2018)
This paper describes the process of development of a Virtual Reality (VR) system which encourages people to exercise and improve their upper-body motor skills after stroke. The system is based on the Buzzwire children’s toy, the physical version of which involves traversing a wire using a loop and wand that closes a circuit and makes a sound when the loop touches the wire. In our VR version users wearing a HMD and holding a tracked wand attempt to traverse a virtual ‘wire’. The ‘wire’ is based on a parametric spline curve and allows us to measure more performance variables than the physical version of the game. The paper describes the initial 2 experiments which test and evaluate aspects of performance, followed by a description of a prototype version of the game. In the first evaluation we tested if performance variables (such as average speed, and distance from the wire) could distinguish between dominant and non-dominant hands of able-bodied subjects. We also compared binocular with monocular viewing. Results showed benefits for dominant over non-dominant hand-control and a dramatic reduction in performance when binocular stereopsis is absent. The second experiment was a usability study involving a sample of stroke affected patients with hemiparesis. Results showed positive acceptance of the technology with no fatigue or nausea and some significant differences between affected and unaffected hand control. Our prototype utilizes learnings from the previous studies to create an enjoyable multi-level version of the game involving auditory guidance as feedback. However, we still require some measure of efficiency of movement by which we can assess kinematic improvements over time.
Keywords: Virtual reality; Interaction techniques; Empirical studies in HCI